Effects of L-arginine on intestinal development and endogenous arginine-synthesizing enzymes in neonatal pigs - Lin Huang; Zong-yong Jiang; Yin-cai Lin; Chun-tian Zheng; Shi-kui Wang; Xue-feng Yang; Guo-yao Wu (African Journal of Pig Farming, 2017)
This study aimed to investigate the effects of dietary L-arginine supplementation on the intestinal development of neonatal piglets and the underlying mechanisms. 36 neonatal piglets were randomly allocated into three diet groups: control group (supplemented with 0% L-arginine), 0.4 and 0.8% L-arginine groups. When compared with the control, dietary supplementation with L-arginine decreased (P<0.05) blood urea nitrogen (BUN), and improved (P<0.05) serum T3 and insulin level of the piglets on day 11. Arginine and its metabolites (citrulline and ornithine) were elevated, additionally, dietary supplementation with 0.8% L-arginine markedly enhanced jejunal villus height, villus area on day 11 and D-xylose absorption rate on day 19. Dietary supplementation with 0.8% L-arginine increased (P<0.05) activities of maltose and lactose on day 18, respectively. This effect correlated with profound change in enzyme activities as inducible nitric oxide synthetase (iNOS), glutamine synthetase (GS) and ornithine decarboxylase (ODC) were elevated on day 18. The concentrations of spermine was increased (P<0.05) by L-arginine supplementation on day 18. These results collectively suggest that dietary L-arginine supplementation improves protein synthesis and intestinal development of the neonatal pigs, the underlying mechanism includes dietary L-arginine supplementation which regulated the productions of intestinal polyamine in jejunum, and stimulated endogenous arginine-synthesizing enzymes in neonatal piglets.